(untitled) (Elmergib Journal of Human Sciences, 2026)
The adverb has its restrictive function in the Arabic language, and this restriction includes a restriction of its agent and its possessor. An adverb may have more than one possessor of an adverb that is appropriate to the context, and with which the composition is correct in wording and meaning. These adverbs with multiple possessives have been applied to Surat Ibrahim; Because it included many adverbs, in which there was a multiplicity of possessors of the adverb, this study was dealt with in three sections: The first section: Explaining the adverb by definition and connotation. The second section: The multiplicity of the adverbs’ possessors, its methods and conditions according to grammarians. The third section: The multiplicity of the adverbs’ possessors for a single adverb in Surat Ibrahim. The research reached a number of results, perhaps the most prominent of which is: that the adverb may have more than one possessor, and all of them are correct. In terms of structure, it is free of weak structure, even if it varies in its strength and priority, and it is correct at the same time in terms of meaning and connotation. In the context of the verses examined, it is possible that the current meaning in them can be attributed to more than one person in a situation.